PERLINDUNGAN HAK EKONOMI TERHADAP LAGU TUHU LA AKU BUAL LAGU YANG DICOVER DALAM CHANEL YOUTUBE - Siburian, Yeremia Elkana Tua; Siregar, Salsabila Balqis; Sihombing, Grace Michael; Peranginangin, Reh Bungana Beru; Siahaan, Parlaungan Gabriel (Universitas Methodist Indonesia, 2023)
Karo songs are works of art created from the Karo language, literature, as well as music and singers. Each word has a specific meaning to convey to the audience, namely the listener/viewer. Economic rights are understood as the right to obtain profits from the creation of a song. This research is an empirical qualitative method, using empirical data collection and in-depth interpretation. The methods used include in-depth interviews and participant observation, the result is that the economic rights of Karo language songs on YouTube are protected, but many individuals also use other people's works for commercial purposes. The protection given to economic rights can be complained of if the content owner reports violations even though copyright ownership has been registered. This is because economic rights adhere to the complaint offense system. Complaints can be submitted through litigation channels, namely the Commercial Court, and also non-litigation channels, namely to the Press council